A FINITE ELEMENT ANALYSIS OF AXISYMMETRIC FLOW OF AIR THROUGH THE TOP RISER OF CASTING USING THE STREAM FUNCTION MODEL (Nigerian Journal of Technology, 2018)
Casting is a manufacturing process for making complex shapes of metal materials. Casting has two stages – filling process requiring a gating system and solidification process requiring a riser. The air in the mould cavity during casting is displaced through the riser by the molten metal in a very rapid manner necessitating the need to understand the air flow behaviour as it exit through the riser. The finite element method and the stream function model were used to analyze the axisymmetric flow of air through the top risers of casting. Results show that the velocity profile at any cross section is parabolic in shape with the maximum velocity at the centre. Comparing results with exact solution shows that the finite element result converged towards the exact solution.\ http://dx.doi.org/10.4314/njt.v37i3.20